High On-Treatment Platelet Reactivity in Patients Undergoing Complex Percutaneous Coronary Interventions - Lukáš Urban MD, PhD; Škorňová Ingrid Ing, PhD; Jana Žolková Ing, PhD; Staško Ján MD, PhD; Tomáš Bolek MD, PhD; Matej Samoš MD, PhD (Clinical and Applied Thrombosis/Hemostasis, 2023)
Patient response to P2Y12 inhibitor therapy is heterogeneous, and those with high on-treatment platelet reactivity (HTPR) are at an increased risk of thrombotic complications. The aim of our study was to determine whether selecting a high-risk patient group of individuals after complex percutaneous coronary intervention (PCI) would show the clinical benefit of HTPR testing for preventing thrombotic complications. Blood samples of patients after complex PCI were acquired 1 day and 1 month after the intervention. The samples were tested using vasodilator-stimulated phosphoprotein phosphorylation (VASP-P) and platelet function assay (PFA). The occurrence of clinically significant stent thrombosis with repeated revascularization of the target vessel was observed over a 1-year period. One day after PCI, 37% of patients had HTPR as established by VASP-P. One month after PCI, the percentage of patients with HTPR decreased to 30.9%. According to PFA, 1 day after PCI, 33.3% of patients had HTPR. This percentage declined to 19.8% after 1 month. All measurements identified a significantly higher proportion of HTPR in patients on clopidogrel compared to ticagrelor and prasugrel. Two cases of early stent thrombosis and 1 case of late stent thrombosis were identified. Further study of adenosine diphosphate receptor blocker on-treatment response in patients undergoing complex PCI is necessary.